Taman Raja Balitung: Stories & Myths As Tourist Attractions - Efariastian Efariastian; Nadia Mawar Janah (Jurnal Indonesia Sosial Teknologi, 2023)
This study focused on analyzing the value and function of Raja Balitung Park and the stories and history of the place in Jongkangan, Tegal Rejo, Tamanmartani, Kalasan District, and Sleman Regency. Particular Region of Yogyakarta. This research uses a qualitative approach, carried out by processing and analyzing data presented in descriptive form. The data source is based on in-depth interviews with resource persons who are natives and guardians of Taman Raja Balitung. The study data is in the form of stories told by resource persons about places visited by King Balitung while hunting, and there are many inscriptions from ancient relics buried in the area of the place, which are then transcribed from interview recordings. The analysis was carried out using Finnegan's study theory, namely the value and function of oral literature. The study results show the historical value of stories contained in the attractions of Taman Raja Balitung, such as the history of naming and the discovery of inscription stones relics of ancient times. Both cultural values are included in stories and myths in Taman Raja Balitung about man's relationship with nature and his relationship with God and beliefs about something.